ADOLESCENT AND ENVIRONMENT: EXPRESSING INNER EXPERIENCES THROUGH NATURAL LANDSCAPES - Kasimova Yulduz Malikovna; Dadaxanova Dilorom (Modern American Journals, 2026)
This article comprehensively analyzes the role of the environment, especially natural landscapes, in expressing the spiritual world and inner experiences of a teenager. Adolescence is one of the most complex and responsible stages in human life, during which processes such as emotional instability, the desire for self-realization, internal conflicts, and adaptation to the social environment intensify. The article examines how these mental states are expressed in fiction through images of nature on a scientific and theoretical basis. Natural landscapes are interpreted as a symbolic tool reflecting the mood, inner experiences, and psychological state of the teenage hero. The analysis of the disclosure of the teenager's spiritual experiences, hopes, fears, and inner searches through the change of seasons in nature, the harmony of colors, weather conditions, and landscape details is carried out.
Keywords: Adolescence, environment, natural landscapes, inner experiences, mental state, artistic image, symbolism, psychological analysis, relationship between man and nature, literary image, aesthetic education, personal development